2006
DOI: 10.1002/eji.200535799
|View full text |Cite
|
Sign up to set email alerts
|

Roles for phosphoinositide 3‐kinases, Bruton's tyrosine kinase, and Jun kinases in B lymphocyte chemotaxis and homing

Abstract: B lymphocyte chemokine receptors signal to downstream effectors by activating heterotrimeric G proteins. However, many of these effectors remain unknown and the known ones often have ill-defined roles in B cell trafficking. Here we report that pharmacological inhibitors of phosphoinositide 3-kinases (wortmannin, WMN), Bruton's tyrosine kinase (LFM-A13), and Jun kinases (SP600125) all significantly impair CXCL12-induced mouse B cell chemotaxis and that of a human B lymphoma cell line. Examination of two CXCR4-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 51 publications
2
37
1
Order By: Relevance
“…This finding contrasts with two previous studies reporting either no change or decreased lymph node homing of WMN-treated B cells (7,16). These differing results could be due to the different time periods of WMN pretreatment and homing analysis among the three studies.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…This finding contrasts with two previous studies reporting either no change or decreased lymph node homing of WMN-treated B cells (7,16). These differing results could be due to the different time periods of WMN pretreatment and homing analysis among the three studies.…”
Section: Discussioncontrasting
confidence: 97%
“…We analyzed B cell homing 4 h posttransfer, whereas other investigators used 1.5 and 2 h (7, 16). Delayed homing is consistent with a report that WMNtreated B cells show reduced adhesion and increased rolling in high endothelial venules (16). It is also possible that WMN causes a delay in homing as well as a block in egress once cells enter the lymph node.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…85 In addition to its role in BCR signaling, BTK is involved in signaling of other receptors related to B-cell migration and adhesion, such as chemokine receptors (CXCR4 and CXCR5) and adhesion molecules (integrins). [86][87][88] Ibrutinib, previously called PCI-32765, binds irreversibly to a cysteine residue (Cys-481) in the BTK kinase domain and inhibits BTK phosphorylation and its enzymatic activity. 89 Byrd et al 14 recently reported that single agent ibrutinib induces an overall response rate of 71% in CLL patients with relapsed or refractory disease and an additional 15% to 20% of patients had a partial response with lymphocytosis.…”
Section: Btk Inhibition In Cll and Other Lymphoid Malignanciesmentioning
confidence: 99%
“…19 In addition to its role in antigen-mediated BCR signaling, Btk is also involved in signaling of other cell-surface receptors, such as the CXCR4 and CXCR5 chemokine receptors and adhesion molecules (integrins) that are essential for B-cell trafficking and tissue homing. [20][21][22] PCI-32765 binds specifically and irreversibly to a cysteine residue in the Btk protein and inhibits Btk phosphorylation on Tyr 223 and consequently its enzymatic activity. 23 PCI-32765 shows encouraging clinical activity in patients with B-cell malignancies, particularly in CLL patients 24,25 ; this response is characterized by a rapid resolution of lymphadenopathy and/or organomegaly, accompanied by a transient surge in lymphocyte counts, presumably because of "mobilization" of tissue-resident CLL cells into the blood.…”
Section: Introductionmentioning
confidence: 99%